SOCIO-LEGAL ANALYSIS OF INDUSTRIAL RELATIONS DISPUTE RESOLUTION DUE TO MASS EMPLOYMENT TERMINATION - Rianza, Riri; Hariansah, Syafri (LPPM STIH Putri Maharaja, 2024)
The closure of five companies in Central Bangka Regency in May 2024 has resulted in mass layoffs of 675 workers. This fact reflects the social and legal reality (dass sein), which shows the weak protection of workers in a corporate crisis triggered by the Attorney General's Office's policy of blocking company accounts to enforce the tin trade law. On the other hand, this condition emphasizes the importance of a fair and crisis-adaptive mechanism for protecting and resolving industrial relations disputes (dass sollen). This study uses a socio-legal approach to evaluate local government interventions' effectiveness in dealing with the' impact of layoffs, including facilitating the disbursement of Old Age Security (JHT) through BPJS Ketenagakerjaan. However, these efforts are still temporary and have not touched on the long-term needs of affected workers. This study highlights the importance of holistic law enforcement, considering cross-sectoral impacts, and encouraging maximising the Job Loss Guarantee (JKP) program and job training as short-term solutions. These findings are expected to contribute to the development of an industrial relations dispute resolution model that is more responsive to the socio-economic context in Central Bangka.